O jovem e o velho Marx: uma cartografia do problema do trabalho - Fernandes, Bruno (2023)
In the Economic and Philosophic Manuscripts of 1844, Marx examines the determinations of estranged work, the act of estrangement (Entfremdung) of human activity. With them, he seeks to show that when the worker is subjugated by the power of the objects he himself created, when his activity is thrust upon him as miserable, he loses the social meaning of his action and corrupts his quality of generic being (Gattungswesen), for the reason for his vital activity is inverted, becoming only a means to his particular existence. Here, estrangement is sustained in opposition to a generic life on the fringe of existence. However, what would happen if this activity were placed within a social history of production? Well, the conception of work would gain new features. This is what we find in The Capital of 1867, where work no longer appears as an activity that must conform to an original sociability, but is seen as a set of physical and mental capacities existing in a man's corporeality (Leiblichkeit) and set in motion by him. Thus, it produces use-values in all epochs, but assumes a specific social form in each one of them. In capitalist society, it takes the form of wage work. This is when work capacity takes on a mercantile form, becoming the basis of the generalized production of commodities. Its main social characteristic is that it assumes for the worker himself the form of a commodity that belongs to him and needs to be sold by him. The confrontation between the free worker and the possessor of money is approached as the product of a historical process of capital's self-valorization that separates the worker from ownership of the conditions for performing his work, engendering a fundamental and open contradiction between capital and work. Considering the tension between these approaches, I investigate the quarrel between the young and the old Marx in order to show the losses of the first model to the detriment of the second, consecrated as a more adequate interpretation of the concept of work in capitalist society.